(untitled) (Economics and region, 2021)
In market conditions, the financial security of the enterprise serves as a guarantee of "survival" and the basis of a stable situation. If the company is financially stable, solvent, it has a number of advantages over other enterprises of the same profile for obtaining loans, attracting investments, choosing suppliers and selecting qualified personnel. The higher the stability of the enterprise, the lower the risk of influence of external and internal factors on its financial security and activities in general. The current crisis situation in the world and in Ukraine, in particular, requires enterprises to respond quickly to the influence of external and internal factors that can both positively and negatively affect the efficiency of the enterprise. Therefore, accelerating the development of enterprises is one of the main tasks of management, which can be solved by developing development drivers. Drivers are a tool for sustainable development of the enterprise through the interaction of financial, socio-economic, industrial and technical and other components of the economic system. It is the drivers who must ensure the detection of deviations from the development trends of the enterprise and the ability to establish the causes of these deviations, as their main task is to find reserves for sustainable growth. Drivers of sustainable development of the enterprise provide an opportunity to monitor daily all business transactions carried out at the enterprise. Analysis of financial security drivers is one of the main reflections of the enterprise, a means of identifying achievements and shortcomings in the work. With the help of this analysis it is possible to influence the work of the enterprise in order to improve it. The assessment of drivers of financial security of the enterprise depends on the correctness of the general characteristics of the financial condition of the enterprise. The main principle for assessing the further development of the enterprise is the requirement to assess all available economic resources of the enterprise in the amount of operating costs and investment costs. The article analyzed the activities of JSC Poltavaoblenergo, established its level of financial security as critical. There are weak points that lead to a decrease in financial stability of the enterprise. To improve the financial condition of the enterprise, the principles of formation of drivers of enterprise development are systematized, which are proposed to be divided into basic and specific ones. The main types of development drivers are considered and their elements are analyzed, which will help to increase the level of financial security of JSC Poltavaoblenergo.